Glycerol dry reforming over Ni supported on fibrous ZSM5 and ZY: Correlation of structural properties on H2 production - Nornasuha, Abdullah; Nurul Aini, Razali; Nor Shuhada Solehah, Hanafi; Herma Dina, Setiabudi; Chin, Sim Yee; Abdul Rahman, Mohamed; Aishah, Abdul Jalil (Elsevier Ltd, 2024)
This study investigates fibrous ZSM5 (FZSM5) and Zeolite Y (FZY) as supports for producing hydrogen via glycerol dry reforming. The fibrous ZSM5 and ZY were synthesized hydrothermally with microemulsion and impregnated with 10 wt% Ni via a sonication method. The catalytic test was conducted via a vertical stainless steel fixed-bed rig, at 800°C with a glycerol/CO2 ratio of 1. XRD and N2 sorption revealed the reduced surface area and crystallinity in Ni/FZSM5 compared to Ni/FZY. Ni/FZY catalyst displayed a larger surface area (264 m2/g) and aperture width (6.70 nm) in comparison to Ni/FZSM5, which had a surface area of 238 m2/g and an aperture width of 3.90 nm. Ni/FZY also had a smaller NiO crystallite size (8.73 nm) than Ni/FZSM5 (9.79 nm), suggesting well-dispersed Ni species on the wrinkle fiber of FZY’s surface. Ni/FZY outperformed Ni/FZSM5 with 52.49% glycerol conversion, 44.87% H2 yield, 71.31% CO yield, and only 14.4% carbon formation, attributed to robust Ni-O-Si contact and larger pore diameter. The discovery highlights the catalytic efficiency of the Ni-loaded fibrous zeolite in GDR, offering versatility for application in energy storage and catalysis.